HUMAN RESOURCE DEVELOPMENT PRACTICES AND EMPLOYEE ENGAGEMENT: A GLOBAL REVIEW OF THE BANKING SECTOR - SABITHA A, DR. T ASOTHAI (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Human Resource Development (HRD) practices are essential for employee engagement, especially within the dynamic and service-based banking sector. This is a synthesis narrative review of national and international literature to look at the issues of HRD interventions, training and development, career planning, performance appraisal, organizational learning, employee welfare, and HRD climate-affecting engagement based on theoretical perspectives of Social Exchange Theory, Job Demand Resources (JD-R) Model, the Engagement Theory and the Self-Determination Theory. Creativity and e-learning, career planning, mentoring, and employee welfare are identified as key research areas in the emerging economy. The study found small number of longitudinal studies, e-HRD research and cross-cultural research as the research gaps. Consecutively, a model of HRD practices is proposed in connection with mediators like psychological factors to employee engagement, perceived organizational support, and empowerment outcomes. The findings have practical implications for banking professionals and scholars in enhancing interest in strategic HRD activities.